The effect of neuroactive steroids in sex differences in the developmental neurotoxicity of the anaesthetic. Issue 2 (1st April 2022) - Li, Ningning; Zhu, Ruilou; Zeng, Shuang; Fu, Ningning; Zhang, Jiaqiang
Abstract: The rapid growth of the number of surgical cases in the world has brought opportunities and challenges to the development of anaesthesia. Modern anaesthesia technology provides safe and effective anaesthesia for hundreds of millions of surgical procedures each year, but there is a lot of concern about the complications (mainly cognitive dysfunction) that occur after anaesthesia exposure. Preclinical studies have demonstrated cognitive dysfunction and behavioural abnormalities that persist into adulthood after exposure to anaesthesia in rodents, revealing the potential neurotoxicity of anaesthetic drugs. In a further study, Sprague–Dawley rats treated with sevoflurane in the first week of life were then subjected to behavioural tests, and female rats were significantly more negatively affected in spatial learning than male rats, suggesting that there may be gender differences in neurotoxicity of the anaesthetic, but the specific mechanisms are unclear. According to the available data, the main hypothesis that can explain the sex difference in the effect of anaesthesia on the central nervous system development remains the difference in hormone levels between males and females. Therefore, this review briefly describes the role of neuroactive steroids in the mechanism of sex differences in neurotoxicity during the development of general anaesthetics. Abstract :